2002
DOI: 10.1093/hmg/11.12.1477
|View full text |Cite
|
Sign up to set email alerts
|

Common haplotypes in five genes influence genetic variance of LDL and HDL cholesterol in the general population

Abstract: We studied the association between common haplotypes in six relevant lipid metabolism genes with plasma lipid levels. We selected single-nucleotide polymorphisms (SNPs) in the cholesterol ester transfer protein (CETP), lipoprotein lipase (LPL), hepatic triglyceride lipase (HL), low-density lipoprotein cholesterol receptor (LDLR), apolipoprotein E (ApoE) and lecithin-cholesterol acyltransferase (LCAT) genes, and studied 732 individuals from 184 German families. Total cholesterol (TC), low-density lipoprotein ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
38
0
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(40 citation statements)
references
References 33 publications
1
38
0
1
Order By: Relevance
“…32 In a large family study on the impact of genetic variants and the effect of SNPs and haplotypes on baseline lipid levels, a similar observation was made for several genes involved in lipid metabolism, including the CETP gene, where haplotypes derived from SNP combinations resulted in stronger significance of the genotypephenotype association than did individual SNPs. 24 CETP protein mass and activity are intermediate phenoypes much closer to the CETP genotype than any other biochemical phenotype (i.e. lipid concentrations).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…32 In a large family study on the impact of genetic variants and the effect of SNPs and haplotypes on baseline lipid levels, a similar observation was made for several genes involved in lipid metabolism, including the CETP gene, where haplotypes derived from SNP combinations resulted in stronger significance of the genotypephenotype association than did individual SNPs. 24 CETP protein mass and activity are intermediate phenoypes much closer to the CETP genotype than any other biochemical phenotype (i.e. lipid concentrations).…”
Section: Discussionmentioning
confidence: 97%
“…Analyses that employ haplotypes, the ordered array of SNP combinations in individual alleles, may enable more consistent and relevant associations. 23,24 In this study, we sought to determine and compare the contribution of individual SNPs and haplotypes in the CETP gene to plasma CETP levels and activity, to lipid levels and to the response to treatment with 3-hydroxy-3-methylglutaray coenzyme A (HMG-CoA) reductase inhibitors (statins) in patients with previously untreated dyslipidemias.…”
Section: Introductionmentioning
confidence: 99%
“…7,[21][22][23][24] Furthermore, other genes such as the ApoE, ApoA1, ApoB, hepatic lipase and PPAR genes have been investigated for their association with lipid levels and/or cardiovascular disease outcomes. 4,10,[25][26][27] Since weight gain and BMI are significantly correlated with serum triglycerides and cholesterol levels, it is possible that genetic variants which may influence the extent of weight gain during treatment with antipsychotics, such as the polymorphisms in the 5-HT2C receptor (À759 T/C), 28,29 polymorphisms of the leptin gene, 28,30 and polymorphisms in the a2A receptor (À1291 C/G) 31 may also be related to deferential drug  gene effects on serum lipids. In this initial study, we could only investigate a few polymorphisms which previous studies suggested may have significant effects on plasma or serum triglycerides or cholesterol; we also chose SNPs with a minor allele frequency of at least 10% in some prior studies.…”
Section: Discussionmentioning
confidence: 99%
“…Polymorphisms in these genes have been shown to influence serum or plasma triglyceride levels [6][7][8] and some of these variations have also been shown to influence cholesterol and other serum lipid parameters. 9 Several studies have revealed pharmacogenetic interactions of polymorphisms in lipid genes and metabolic response to statin drug treatment (for a review see Knoblauch et al 10 ; Schmitz et al 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…They did. 24 We then expanded this analysis to 7 additional genes. With common single nucleotide polymorphisms in 13 genes, we were able to construct haplotypes that account for approximately two-thirds of the Luft Geneticismgenetic variance for LDL and HLD.…”
mentioning
confidence: 99%